Improved treatment and prognosis after acute myocardial infarction in Estonia: cross-sectional study from a high risk country. Issue 1 (December 2015) - Saar, Aet; Marandi, Toomas; Ainla, Tiia; Fischer, Krista; Blöndal, Mai; Eha, Jaan
Abstract Background The aim of the study was to explore trends in short- and long-term mortality after hospitalization for acute myocardial infarction (AMI) over the period 2001─2011 in Estonian secondary and tertiary care hospitals while adjusting for changes in baseline characteristics. Methods In this nationwide cross-sectional study random samples of patients hospitalized due to AMI in years 2001, 2007 and 2011 were identified and followed for 1 year. Trends in 30-day and 1-year all-cause mortality were analysed using Cox proportional hazards regression model. Results The final analysis included 423, 687 and 665 patients in years 2001, 2007 and 2011 respectively. During the study period, the prevalence of most comorbidities remained unchanged while the in-hospital and outpatient treatment improved significantly. For example, the proportion of tertiary care hospital AMI patients who underwent revascularization was almost three times higher in 2011 compared to 2001. The proportion of secondary care patients who were referred to a tertiary care centre for more advanced care increased from 5.8 to 40.1 % (p for trend <0.001). Meanwhile, the 1-year mortality rates decreased from 29.5 to 20.2 % (adjustedp  = 0.004) in the tertiary and from 32.4 to 23.1 % (adjustedp  = 0.006) in the secondary care. The decrease in the 30-day mortality rates was statistically significant only in the secondary care hospitals. Conclusions The use of evidence-based treatments in Estonian AMI patients improved between 2001 and 2011. At the same time, we observed a significant reduction in the long-term mortality rates, both for patients primarily hospitalized into secondary as well as into tertiary care hospitals.